Enhancing Product Value through Vegetable Processing Training in Dukuh Mecek Village, Jember District - Azkiyah, Lailatul; Witono, Yuli; Dwi Pamujiati, Agustia; Fauzi, Mukhammad; Dwi Masahid, Ardiyan; Salsabila Yusviva, Galuh; Rosiana Yunianto, Gading (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The Cempakaan Dukuh farmer group in Dukuh Mencek Village, Sukorambi District, Jember Regency, actively cultivates various vegetables. Currently, this farmer group lacks knowledge and skills in processing technology for vegetable-based food products. As a result, their vegetable harvests are mainly sold in fresh form, either directly to consumers or through intermediaries, which keeps their selling prices low. To address this issue, a training program was implemented to enhance the farmers' understanding and skills in processing technology, specifically focusing on creating water spinach jerky and spinach sticks. The training involved several steps: organizing coordination meetings to prepare for the activities, delivering the training materials, facilitating discussions, and providing hands-on practice. Finally, the outcomes of the service were evaluated and reviewed. The results of the training showed that the farmer group was enthusiastic about participating in the community service activities. To evaluate their progress, pre-test and post-test assessments were conducted. The pre-test scores for each question were 56, 32, 54, 48, 40, and 45, while the post-test scores were 87, 83, 86, 80, 75, and 73. The increase in post-test scores indicates a significant improvement in the farmers' ability to utilize technology for processing water spinach jerky and spinach sticks.